Bharata Natyam training at The Temple of Fine Arts: Pre arangetram, arangetram and post- arangetram / Bhanumathi K Nadson - Bhanumathi , K Nadson (2019)
Solo debut recital called arangetram is an essential part of training in Indian classical dance, particularly, Bharata Natyam. Years of training in Bharata Natyam usually culminates with the staging of the major and sometimes “spectacle” recital, arangetram. While it is looked upon as a means to introduce the dancer to the public and launch his/her dance career, scholars of Indian dance have variously argued that arangetrams often lead to the degeneration of dance careers. However, I do not see this trend in my study which focuses on Bharata Natyam training at the Temple of Fine Arts (TFA). The TFA Kuala Lumpur was inaugurated in 1981 by its patron, the late His Holiness Swami Shantanand Saraswati. It is one of the leading institutions of Indian classical dances in Malaysia. TFA has branches in Penang, Johor Bahru, Malacca in Malaysia as well as branches in other countries such as Singapore, Colombo in Sri Lanka, Perth in Australia, Coimbatore and Chennai in Tamil Nadu, South India and in New Zealand. Bharata Natyam is the oldest and most popular Indian classical dance form taught in TFA for more than three decades now. Not only is the training unique as it adheres to the traditional guru-sishya relationship despite institutional training that is based on exams, it also provides a pathway for students to emerge as soloists and choreographers through different platforms. This study will trace that pathway by focusing on phases of pre-arangetram, arangetram, and post-arangetram. While this study highlights challenges and problems in launching a career as a performer and choreographer in Indian classical dance in Malaysia, it will also demonstrate how arangetram is a gateway that helps to shape one as a public performer. TFA goes one step further and provides a platform for its graduates to emerge as soloists, group performers, and choreographers, continuously nurturing the artistic growth of its students. In this dissertation, I will examine the training methods that culminate with TFA arangetram and further investigate what happens to dancers at post-arangetram phase by looking at several dance performances. This study draws materials from ethnographic research conducted with teachers, graduates of TFA, students, parents and management.